Patriarchal Propaganda on Archipelagic Folklores - Sufa, Amy Fayla (Journal of Language and Literature, 2023)
A folklore is a patriarchal propaganda, by carrying out stories that indoctrinate how mankind should behave, or how men and women have their role in society. This study aims to discover the patriarchal construct in archipelagic folklore and how archipelagic folklore gave rise to propaganda to the current patriarchal system. This study used a qualitative descriptive method using a mimetic and objective approach. The process of collecting data is through library study including sources taken from texts in the book "The Collection of Folklore in 33 Provinces” by the publisher Lingkar Media, and the animated video of The Archipelago Story on YouTube from the channel Gromore Studio. Furthermore, this study found there are 11 constructs of patriarchy contained in the archipelagic folklore in selected legends. As the result, the intention of patriarchal culture rooted in Indonesia and existing in the current times did not only came from one direction, but from several directions which then gave rise to a complex understanding. It is influenced by the culture of the colonial foreign countries and the fundamental beliefs of its society even before the colonialism era. The archipelagic folklore is one of a tool for spreading implicit messages that contain a deep meaning, patriarchalism.